Neuronal subset-specific Pten-deficient mice do not exhibit deficits in sensorimotor gating processes [version 4; peer review: 1 approved, 2 approved with reservations] - Matthew S. Binder; Joaquin N. Lugo; Suzanne O. Nolan (F1000Research)
Background Deficits in sensorimotor gating have been reported in individuals with autism spectrum disorder (ASD), as well as in ASD murine models. However, this behavior has not been examined in the neuronal subset-specific (NS)-Pten knockout (KO) model of ASD. NS-Pten KO mice exhibit hyperactivity of the PI3K/AKT/mTOR signaling pathway which is implicated in the onset of autistic deficits. This study investigates the potential relationship between PI3K/AKT/mTOR signaling and deficits in sensorimotor gating. Methods To assess sensorimotor gating in NS-Pten KO mice we utilized a three-day paradigm. On day 1 (habituation) the mice were administered 80 repetitions of a 120-dB startle stimulus. On day 2, prepulse inhibition was measured with 90 trials of the startle stimulus that was paired with a smaller (2, 7, or 12 dB) prepulse stimulus. Day 3 was assessed one week later, consisting of randomized startle trials and trials with no stimulus and was used to determine the startle response. Results No significant difference between NS-Pten KO or wildtype (WT) mice was found for habituation (p > 0.05). No significant differences were found between groups when assessing the percentage of prepulse inhibition at 2, 7, and 12 dB (p > 0.05). There was also no difference in startle response between groups (p > 0.05). Conclusion Our study found that the NS-Pten KO model does not display significant deficits in sensorimotor gating processes. The present findings help to elucidate the relationship between PI3K/AKT/mTOR hyperactivation and sensory reactivity.